Characterization of the Characters in The Pursuit Of Happyness Movie - Ratih, Ni Wayan Nari; Buadiarsa, Made; Primahadi Wijaya Rajeg, Gede (Udayana Journal of Social Sciences and Humanities; Vol 6 No 1 (2022): UJoSSH, February 2022, 2022)
This study intended to identify the types of the main and secondary character and to describe the characterization method used by the author to represent the characters in the movie. This study applied the theory proposed by William Kenney (1966) in the book How to Analyze Fiction and the theory by Pickering and Hoeper (1962) in the book Concise Companion to Literature. The data of this study were analyzed by descriptive qualitative method. The result of this study shows the types of characters, which ar e Chris Gardner and Christopher. Based on the data analysis, they are can be categorized as round character. The author used telling method of characterization to represent the characters through their appearance. H e is also used showing method of characterization through the dialogue between the characters and their action.